Investigation of properties of Aluminium Based Nanocomposite Reinforced with Biologically Synthesized Silver Nanoparticles. (2018) - Lata, Surabhi; Kumar Verma, Nitish; Sharma, Aayush; Gupta, Nitesh; Chopra, Daksh; Singh, Chetan
Abstract: A shift from monolithic materials to composites to nanocomposites has become an urge to sustain the endlessly growing manufacturing, automobile and aerospace industries. This newly formed class of materials is expanding for newer exploration and research. This research work investigates the mechanical properties of Al 6082 based composites, green synthesized silver nanoparticles through reduction of AgNO3 with the Aloe Barbendis (Indian name: Aloe Vera) as reducing agent and consolidated by stir casting to fabricate silver nanoparticle reinforced nanocrystalline Al composites (1% by wt. Ag). The X-Ray diffraction annd UV-Vis spectroscopy of silver nanoparticles confirms the formation of the silver nanoparticles which later is used as reinforcement. The tensile and compression test on composite confirms the increase in brittle nature of composite. The Brinell hardness test of the composite shows the decrease in hardness by 25.4 BHN while the Charpy and Izod test exhibit low absorbance of energy. It can be concluded that nanocomposites are the new materials comprising of properties of different metals along with the anti-bacterial and anti-fungal properties, contributing towards the eco-friendly world.